Search for lepton-flavour-violating H → μτ decays of the Higgs boson with the ATLAS detector - Alconada Verzini, María Josefina (2015)
A direct search for lepton-flavour-violating H → μτ decays of the recently discovered Higgs boson with the ATLAS detector at the LHC is presented. The analysis is performed in the H → μτhad channel, where τhad is a hadronically decaying τ-lepton. The search is based on the data sample of proton-proton collisions collected by the ATLAS experiment corresponding to an integrated luminosity of 20.3 fb-1 at a centre-of-mass energy of √s = 8TeV. No statistically signi cant excess of data over the predicted background is observed. The observed (expected) 95% con dence-level upper limit on the branching fraction, Br(H → μτ), is 1.85% (1.24%).